# F(x) = x+3-2x3-1 for x ≠ 1 = 2 for x = 1, at x = 1. - Mathematics and Statistics

Sum

f(x) = (sqrt(x + 3) - 2)/(x^3 - 1)  for x ≠ 1

= 2    for x = 1, at x = 1.

#### Solution

f(1) = 2  …[given]

lim_(x→1) "f"(x) = lim_(x→1) (sqrt(x + 3) - 2)/(x^3 - 1)

= lim_(x→1) ((sqrt(x + 3) - 2)/(x^3 - 1) xx (sqrt(x + 3) + 2)/(sqrt(x + 3) + 2))

= lim_(x→1) ((x + 3 - 4)/((x^3 - 1)(sqrt(x + 3) + 2)))

= lim_(x→1) (x - 1)/((x - 1)(x^2 + x + 1)(sqrt(x + 3) + 2))

= lim_(x→1) 1/((x^2 + x + 1)(sqrt(x + 3) + 2)) ...[("As"  x→1","  x ≠ 1),(therefore x - 1 ≠ 0)]

= 1/(lim_(x→1)(x^2 + x + 1) xx lim_{x→1} (sqrt(x + 3) + 2))

= 1/((1^2 + 1 + 1) xx (sqrt(1 + 3) + 2))

= 1/(3(2 + 2))

= 1/12

∴ lim_(x→1) "f"(x) ≠ "f"(1)

∴ f is discontinuous at x = 1

Concept: Continuity in the Domain of the Function
Is there an error in this question or solution?
Chapter 8: Continuity - Miscellaneous Exercise 8 [Page 113]

#### APPEARS IN

Balbharati Mathematics and Statistics 1 (Commerce) 11th Standard Maharashtra State Board
Chapter 8 Continuity
Miscellaneous Exercise 8 | Q I. (4) | Page 113
Share